2010
DOI: 10.1016/j.jchromb.2010.08.034
|View full text |Cite
|
Sign up to set email alerts
|

A general HPLC–UV method for the quantitative determination of curcumin analogues containing the 1,5-diaryl-3-oxo-1,4-pentadienyl pharmacophore in rat biomatrices

Abstract: Curcumin and its derivatives generally display favorable cytotoxic activities against a number of cancer cell types. We focus our rational antineoplastic drug design program on curcumin analogues containing the 1,5-diaryl-3-oxo-1,4-pentadienyl pharmacophore. Favorable outcomes from pharmacological screens of this series demanded further pharmacokinetic evaluations to determine their suitability as effective compounds in vivo. To allow such evaluations and to provide a general, sensitive, rapid and simple metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…It has been reported that curcumin has many pharmacological functions, such as antioxygenation, antibiosis and antitumor [1][2][3] . Methods such as high-performance thin-layer chromatographic (HPTLC) [4][5][6][7] , high-performance liquid chromatography (HPLC) [8][9][10][11] , capillary electrophoresis with amperometric detection (CE-AD) 12 , matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOFMS) 13 , spectrofluorimetry 14,15 , liquid phase tandem mass spectrometry (LC-MS/MS) 16,17 , 1 H NMR 17 , resonance light scattering technique (RLS) 18 and spectrophotometry [19][20][21] have been employed to determine curcumin in a variety of matrixes. However, most of these methods have low sensitivity, need a large number of organic solvents or metal ions.…”
Section: Curcuminmentioning
confidence: 99%
“…It has been reported that curcumin has many pharmacological functions, such as antioxygenation, antibiosis and antitumor [1][2][3] . Methods such as high-performance thin-layer chromatographic (HPTLC) [4][5][6][7] , high-performance liquid chromatography (HPLC) [8][9][10][11] , capillary electrophoresis with amperometric detection (CE-AD) 12 , matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOFMS) 13 , spectrofluorimetry 14,15 , liquid phase tandem mass spectrometry (LC-MS/MS) 16,17 , 1 H NMR 17 , resonance light scattering technique (RLS) 18 and spectrophotometry [19][20][21] have been employed to determine curcumin in a variety of matrixes. However, most of these methods have low sensitivity, need a large number of organic solvents or metal ions.…”
Section: Curcuminmentioning
confidence: 99%
“…Various role including antioxidant, anti-inflammatory, antibacterial, antiviral, anti-atherosclerotic, anti-arthriticagent and anticancer activities [16][17][18][19] are logical reasons for its extensive application and encourage researchers to design an accurate approach for preconcentration and quantification of curcumin in low level in complicated matrices. Several methods such as high-performance liquid chromatography [20][21][22], thin layer chromatography [23], UV-Vis spectrophotometry [24], HPTLC [25], 2-D flash liquid chromatography [26] and spectrofluorimetry [27,28] are applied for this regard. HPLC method compared to other techniques benefit from remarks like high reliability and efficiency and selectivity is appropriate for analyzing real samples with complex matrices, while for analytes with extremely low concentration a preliminarily preconcentration help the researchers to reduce the interference correspond to other constituents and simultaneously improve the performance of proposed method [29].…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been used for the analysis of curcumin, including UV-Vis spectrophotometry, high-performance thin-layer chromatography (HPTLC), and high-performance liquid chromatography (HPLC) (Bos et al, 2007;Mandal et al, 2008;Pozharitskaya et al, 2008;Wichitnithad et al, 2009;Singh et al, 2010). However, all these methods have the disadvantages of low sensitivity, multiple procedural steps and considerably high cost.…”
Section: Introductionmentioning
confidence: 99%